TEACHING SPEECH ACTS AND INTONATION AS MEANS OF EXPRESSING MOTIVATION TO ACTION - Alisherova Madinabonu Murodiljon qizi; Hasanova Dinora Sherali qizi; Ahmedov Islom Sattorqul o'g'li; Niyazova Dildora Furqatovna (TADQIQOTLAR, 2025)
Abstract. This article examines the role of speech acts and intonation in the formation of communicative speech, their functions as a means of motivating students to action. The pragmatic nature of speech acts, the importance of intonation in conveying meaning and emotional tone are analyzed scientifically and theoretically. Also, effective methods of teaching these units, practical exercises, communication- oriented tasks and mechanisms for their use in the lesson process are presented. The article concludes with recommendations aimed at strengthening the pragmatic approach to language teaching and developing students’ active communicative competence.